On the Virtualization of Wireless Links - van de Belt, Jonathan (Trinity College Dublin. School of Computer Science & Statistics, Discipline of Computer Science, 2018)
This thesis is concerned with the virtualization of wireless links. Initially, the sole aim of this thesis was to investigate the virtualization of wireless networks. However, soon after first investigating this topic it became apparent that the term ‘virtualization’ is not used in a precise or meaningful manner in current technical work, and that the largest obstacle to wireless network virtualization is the virtualization of wireless links. Therefore, although investigating wireless link virtualization is the primary goal of the thesis, a secondary objective of the thesis is to clarify virtualization in a general context. This opening chapter of the thesis demonstrates the lack of meaning surrounding the term ‘virtualization’ in more detail, before laying out the objectives and contributions of this thesis
Keywords: wireless networks